Serial Evaluation of Haemostasis Following Acute Trauma Using Rotational Thromboelastometry in Cats - Muri, Benjamin M.; Jud Schefer, Rahel; Sigrist, Nadja E. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to describe coagulation abnormalities and incidence of acute traumatic coagulopathy (ATC) in traumatized cats over the first 24 hours after admission.Study Design This was a prospective observational study at the university teaching hospital including 26 cats with acute (<5 hours) trauma. Blood was sampled for rotational thromboelastometry (ROTEM) parameters at presentation and 6 hours/24 hours thereafter. Rotational thromboelastometry tracings were defined as hypo- or hypercoagulable if ≥ 2 of the following parameters were above or below institutional reference intervals: clotting time, clot formation time (CFT), maximum clot firmness, maximum lysis or maximum clot elasticity. Hypocoagulability at presentation was defined as ATC. Injury severity scores, treatment and survival to hospital discharge were retrieved from patient records.Results The incidence of ATC was 15% and the most common ROTEM abnormalities in cats with ATC were clotting time and CFT prolongation in both extrinsic and intrinsic ROTEM profiles. After 24 hours, compared with presentation, significantly more cats were hypercoagulable (p = 0.047) and none of the cats showed hypocoagulopathy. Cats with ATC received significantly more blood transfusions (p = 0.008).Conclusion The incidence of ATC in cats is higher than previously reported. Clotting time and CFT prolongations seem to be more common than hyperfibrinolysis and 53% of the cats became hypercoagulable within 24 hours. While the clinical relevance of ATC in cats needs to be investigated, cats diagnosed with ATC required significantly more blood transfusions.
Keywords: ATC; ACoT; coagulation; fibrinolysis; acute traumatic coagulopathy